Determination of the Assessment System for German Language Learning Based on the Merdeka Curriculum in West Seram and Central Maluku - Jolanda Tomasouw; Juliaans E. R. Marantika; June Carmen Noya van Delzen; Piet Soumokil; Vithalia Daskunda; Rita Fransina Maruanaya (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
This research aims to evaluate the assessment system for German language learning based on the Merdeka Curriculum in the West Seram and Central Maluku regions. Utilizing a descriptive qualitative method, data were collected through questionnaires, interviews, and document analysis. The findings indicate a contradiction where 65% of teachers perceive the current assessment quality as inadequate, yet the same percentage also believe it meets educational needs, highlighting a disparity between perception and practice. The study recommends adopting a more comprehensive, competency-based assessment model to better align with the Merdeka Curriculum. The current assessments are predominantly focused on cognitive aspects, lacking integration of speaking and listening skills. This study identifies challenges in implementing the Merdeka Curriculum, including limited resources and varying teacher understanding. Proposed recommendations include the adoption of a more comprehensive competency-based assessment system, authentic assessments, performance rubrics, and portfolios to document student progress. It is hoped that the results of this research will enhance the quality of German language learning and effectively support the implementation of the Merdeka Curriculum.